Smart generic cabling and network planning in office network. (2017) - Xu, Banghai; Wang, Ruofeng; Su, Wanli
Smart city intelligently responses to various requirements including environmental protection, public security, urban services, commercial and industrial activities, etc. Smart city deals with lots of key information in the whole city by utilising modern technologies like communication technology. Enterprise network is an enormous and complex system belonging to smart city. It not only provides basic platforms of office automation but also various application services, where information can be delivered to other systems. In this paper, we design a generic cabling according to the requirement of enterprise networks. Our generic cabling is well extensible and compatible. In addition, we also present the network planning for enterprise network such that it provides good service for the whole enterprise.